Interpersonal Synergies - Riley, Michael A.; Richardson, Michael; Shockley, Kevin; Ramenzoni, Verónica C. (Frontiers in Psychology, 2011)
We present the perspective that interpersonal movement coordination results from establishing interpersonal synergies. Interpersonal synergies are higher-order control systems formed by coupling movement system degrees of freedom of two (or more) actors. Characteristic features of synergies identified in studies of intrapersonal coordination—dimensional compression and reciprocal compensation—are revealed in studies of interpersonal coordination that applied the uncontrolled manifold approach and principal component analysis to interpersonal movement tasks. Broader implications of the interpersonal synergy approach for movement science include an expanded notion of mechanism and an emphasis on interaction-dominant dynamics.